CURRENT STATE OF THE REPUBLIC'S SILK INDUSTRY AND PROSPECTS FOR ITS DEVELOPMENT - Kodirov Ziyodulla Abdumukhtarovich (Ecominds Press, 2025)
This article analyzes the current state of the sericulture industry of our republic and the prospects for its development. The forces that negatively affect the cocoon shell during the processes of preparation, transportation, storage and preliminary processing of cocoons, which are the main raw material of cocoon enterprises, are theoretically studied. The values of the forces acting on the cocoon during the mixing of cocoons with wooden shovels at cocoon reception points are also determined.
Keywords: Cocoon, silk, silk fiber, sericulture, steaming, cocoon steaming device, cocoon shell, mixing, speed, acceleration, damage, experiment.